2004
DOI: 10.1007/s00702-004-0117-z
|View full text |Cite
|
Sign up to set email alerts
|

Dyslexia: the possible benefit of multimodal integration of fMRI- and EEG-data

Abstract: Biological research about dyslexia has been conducted using various neuroimaging methods like functional Magnetic Resonance Imaging (fMRI) or Electroencephalography (EEG). Since language functions are characterized by both distributed network activities and speed of processing within milliseconds, high temporal as well as high spatial resolution of activation profiles are of interest: "where" can dyslexia specific activations be detected and "when" do language processes start to diverge between dyslexics and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 14 publications
4
36
1
1
Order By: Relevance
“…Underactivation in the middle portion of the middle temporal gyrus occurred in a study employing a pseudoword rhyming task (Grunling et al, 2004). Thus, also the anterior MTG underactivation may reflect a deficit in phonological processing.…”
Section: Discussionmentioning
confidence: 98%
“…Underactivation in the middle portion of the middle temporal gyrus occurred in a study employing a pseudoword rhyming task (Grunling et al, 2004). Thus, also the anterior MTG underactivation may reflect a deficit in phonological processing.…”
Section: Discussionmentioning
confidence: 98%
“…Only 2 adult studies relied on a more liberal threshold which may have inflated the number of input foci (Brambati et al, 2006;Rumsey et al, 1997). However, the comparatively large number of overactivation foci from adult studies does not result from these two studies with the more liberal thresholds, but from the two studies from our lab with German dyslexic participants Wimmer et al, 2010; see also Grünling et al, 2004).…”
Section: Differences In Data Acquisition and Analysismentioning
confidence: 89%
“…In addition, we included a recent large study (presented as a poster) from a multi-center project in which our lab was involved (Maurer et al, 2010). To clearly differentiate between children and adults, 4 studies with adolescents were excluded (Georgiewa et al, 1999;Grünling et al, 2004;Hoeft et al, 2007;Kronbichler et al, 2006). Two further studies Schulz et al, 2008) were excluded in favor of more recent ones with the same participants (Meyler et al, 2008;Schulz et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…Notably, developmental changes in right TPJ activation have been linked to reading acquisition in normally developing children (Turkeltaub, Gareau, Flowers, Zeffiro & Eden, 2003) and some studies have observed a right TPJ deficiency in dyslexics (e.g. Hoeft et al, 2006;Grü nling et al, 2004).…”
Section: Discussionmentioning
confidence: 99%